Antibiotic profiling of Clostridium difficile ribotype 176--A multidrug resistant relative to C. difficile ribotype 027 - Krůtová, Marcela; Matějková, Jana; Tkadlec, Jan; Nyč, Otakar (Anaerobe, 2015)
Antibiotic profiling of twenty Czech Clostridium difficile PCR-ribotype 176 isolates revealed a high level of resistance to erythromycin, ciprofloxacin and moxifloxacin (n = 20) and to rifampicin (n = 13). Accumulation of resistance mechanisms to multiple antibiotics highlight that PCR-ribotype 176 belong to problematic epidemic strains.
Keywords: Humans; sekvence nukleotidů; Ribotyping; mnohočetná bakteriální léková rezistence; Molecular Sequence Data; molekulární sekvence - údaje; mutace; lidé; antibakteriální látky; ribotypizace; bakteriální proteiny; Drug Resistance, Multiple, Bacterial; pseudomembranózní enterokolitida; Anti-Bacterial Agents; Base Sequence; Czech Republic; Enterocolitis, Pseudomembranous; Bacterial Proteins; Mutation; Česká republika; Clostridioides difficile